2022
DOI: 10.3390/nu14071390
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidant, Anti-Platelet and Anti-Coagulant Properties of Phenolic Compounds, Associated with Modulation of Hemostasis and Cardiovascular Disease, and Their Possible Effect on COVID-19

Abstract: Patients affected by coronavirus disease 2019 (COVID-19) demonstrate a range of hemostasis dysfunctions, such as coagulation dysfunction and changes in blood platelet function, this being a major cause of death. These complications may also be associated with oxidative stress. Recently, various papers, including some reviews, have suggested that the use of dietary bioactive compounds, including phenolic compounds, may play a significant role in the treatment of COVID-19. However, while some phenolic compounds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
(103 reference statements)
1
6
0
1
Order By: Relevance
“…Recent study in Egypt revealed that medicinal plants have possessed high active metabolites for inhibition of Coronavirus [ 53 ]. The results from this study are supported by previous works that revealed the antiviral activity of herbal medicines though ant oxidation, anticoagulation and anti-inhibitory activity of natural phenolic compounds [ 54 – 56 ]. Several efforts toward discovery of SARS Cov-2 have been investigated though preclinical and clinical trials [ 57 ].…”
Section: Discussionsupporting
confidence: 90%
“…Recent study in Egypt revealed that medicinal plants have possessed high active metabolites for inhibition of Coronavirus [ 53 ]. The results from this study are supported by previous works that revealed the antiviral activity of herbal medicines though ant oxidation, anticoagulation and anti-inhibitory activity of natural phenolic compounds [ 54 – 56 ]. Several efforts toward discovery of SARS Cov-2 have been investigated though preclinical and clinical trials [ 57 ].…”
Section: Discussionsupporting
confidence: 90%
“…The flavonol quercetin is a well-known antiplatelet compound which can inhibit platelet aggregation through various signaling pathways and, thus, may play a crucial role in the prevention of thrombosis and cardiovascular disease [64,65]. Furthermore, the anticoagulant and anti-platelet effects of quercetin can be beneficial for treating viral diseases such as COVID-19, since the infection may initiate thrombotic events through changes in platelet aggregation [66]. Thus, quercetin received attention during the COVID-19 pandemic because of its versatile anti-SARS-CoV-2 effects [67][68][69].…”
Section: Human Researchmentioning
confidence: 99%
“…K E Y W O R D S bioactive compounds, Covid-19, curcuminoids, extraction techniques, health benefits 1 | INTRODUCTION Curcuminoids are bioactive components extracted from rhizomes of Curcuma longa, an annually growing herb belongs to the family ofZingiberaceae. In Asian middle-east countries, turmeric is used as spice, preservative, food additive, coloring agent, as medicine, and consumed daily for many culinary applications (Khan et al, 2022;Olas, 2022;Zhang & Kitts, 2021). Curcuminoids are a family of bioactive components present in turmeric that constitutes upto 1%-6% by weight and distributed as curcumin (Cur), demethoxycurcumin (DMC), and bisdemethoxycurcumin (BDMC).…”
mentioning
confidence: 99%
“…These compounds are linear, diarylheptanoid molecules, arguably one of the highly investigated phytochemical that vary in chemical structures and functional properties (Amalraj et al, 2017).Curcuminoids are lipophilic natural chemical compounds that contain wide variety of therapeutic properties. Generally, they act as natural ligands with peroxisome proliferator-activated receptor-γ, which has the ability to reduce production of cytokine, and thus they function as anti-inflammatory, antioxidant, antiviral, and anticancer agent (Olas., 2022;Yang et al, 2023;Yang et al, 2023;Zahedipour et al, 2020). Many studies have demonstrated that curcumin, the primary pigment in turmeric, exhibits a wide range of in vivo pharmacological activities, such as cardio-protective, hepato-protective…”
mentioning
confidence: 99%
See 1 more Smart Citation